Clustering of venous thrombosis events at the start of tamoxifen therapy in breast cancer: A population-based experience - Onitilo, Adedayo A. (2011)
INTRODUCTION: The epidemiology of tamoxifen and venous thromboembolism (VTE) is not well understood, and most data on tamoxifen toxicity are from adjuvant clinical trials. This study examined the relationship between the duration of tamoxifen use in female patients with breast cancer and the risk of VTE in a large population-based setting. MATERIALS AND METHODS: Retrospective electronic data extraction on tamoxifen utilization was undertaken among a cohort of 3572 women with breast cancer seen at Marshfield Clinic between January 1, 1994 and June 31, 2009. Observational follow-up extended until February, 2010. RESULTS: On initial exposure to tamoxifen, women had a clustering of VTE events. Cox proportional hazards regression, adjusting for multiple clinically-important covariates including age, body mass index, cancer stage, and concurrent diabetes, demonstrated that as use of tamoxifen continued in those without earlier VTE events, risk of subsequent VTE gradually increased, albeit at a lower rate (hazard ratio per year of tamoxifen duration=1.225, P <0.0001). CONCLUSIONS: In our study population, initiating tamoxifen coincided with an initial clustering of VTE events, with risks due specifically to tamoxifen, increasing during continued exposure. Evidence suggested that the VTE clustering occurred in high risk individuals at initiation of tamoxifen therapy. Careful selection of patients for whom tamoxifen therapy is appropriate based on susceptibility to VTE is thus required prior to initiation of therapy.